The unequal influences of the left and right vagi on the control of the heart and pulmonary artery in the rattlesnake, Crotalus durissus - Taylor, E. W. [UNESP]; Andrade, Denis V. [UNESP]; Abe, Augusto Shinya [UNESP]; Leite, Cleo A. C. [UNESP]; Wang, Tobias [UNESP] (Company of Biologists Ltd, 2009)
Autonomic control of the cardiovascular system in reptiles includes sympathetic components but heart rate (f(H)), pulmonary blood flow (Q(pul)) and cardiac shunt patterns are primarily controlled by the parasympathetic nervous system. The vagus innervates both the heart and a sphincter on the pulmonary artery. The present study reveals that whereas both the left and right vagi influence f(H), it is only the left vagus that influences pulmonary vascular resistance. This is associated with the fact that rattlesnakes, in common with some other species of snakes, have a single functional lung, as the other lung regresses during development. Stimulation of the left cervical vagus in anaesthetised snakes slowed the heart and markedly reduced blood flow in the pulmonary artery whereas stimulation of the right cervical vagus slowed the heart and caused a small increase in stroke volume (V(S)) in both the systemic and pulmonary circulations. Central stimulation of either vagus caused small (5-10%) reductions in systemic blood pressure but did not affect blood flows or f(H). A bilateral differentiation between the vagi was confirmed by progressive vagotomy in recovered snakes. Transection of the left vagus caused a slight increase in f(H) (10%) but a 70% increase in Q(pul), largely due to an increase in pulmonary stroke volume (V(S,pul)). Subsequent complete vagotomy caused a 60% increase in f(H) accompanied by a slight rise in Q(pul), with no further change in V(S,pul). By contrast, transection of the right vagus elicited a slight tachycardia but no change in V(S,pul). Subsequent complete vagotomy was accompanied by marked increases in f(H), Q(pul) and V(S,pul). These data show that although the heart receives bilateral vagal innervation, the sphincter on the pulmonary artery is innervated solely by the left vagus. This paves the way for an investigation of the role of the cardiac shunt in regulating metabolic rate, as chronic left vagotomy will cause a pronounced left-right shunt in recovered animals, whilst leaving intact control of the heart, via the right vagus.
Keywords: cardiovascular; nervous control; reptile